Silicon carbide composition, silicon carbide ceramic and preparation method thereof
By using a modified silicon carbide composition, including the modified silicon carbide whiskers and silicon dioxide film layer after pre-oxidation treatment, the problems of poor sintering performance and high porosity of the silicon carbide ceramic materials are solved, and higher fracture toughness and tensile strength are achieved.
Patent Information
- Application Number
- CN202510165550.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing preparation methods for silicon carbide whisker-reinforced silicon carbide ceramics, the addition of silicon carbide whiskers increases the difficulty of sintering, resulting in poor sintering performance of the material, prone to residual pore problems, and the bonding strength between the whiskers and the silicon carbide ceramic matrix is not high, making it difficult to fully exert the interface strength of the whiskers.
Using a modified silicon carbide composition, including modified silicon carbide whiskers, silicon carbide particles, sintering aids and binders, the modified silicon carbide whiskers are coated with a silicon dioxide film layer by pre-oxidation treatment to improve their compatibility with the sintering aid and sintering activity, and enhance the interface bonding strength with the silicon carbide matrix.
The porosity of silicon carbide ceramics is significantly reduced, its fracture toughness and tensile strength are improved, and the toughening effect of silicon carbide whiskers is fully utilized.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material preparation, and in particular to a silicon carbide composition, a silicon carbide ceramic and a preparation method thereof. Background Art
[0002] Silicon carbide whisker reinforced silicon carbide ceramics are new composite materials that combine the basic properties of ceramics with the reinforcement effect of whiskers, significantly improving the toughness and strength of the material. Silicon carbide whisker reinforced silicon carbide ceramic materials have excellent corrosion resistance, high temperature resistance and wear resistance; they also have good fracture toughness, and have better application potential than traditional short fiber reinforced ceramics.
[0003] However, in the current preparation method of silicon carbide whisker reinforced silicon carbide ceramics, the addition of silicon carbide whiskers increases the difficulty of sintering, and is prone to poor sintering performance of silicon carbide ceramic materials and residual pores at the whiskers. In addition, silicon carbide whiskers are highly crystalline, and their bonding strength with the silicon carbide ceramic matrix is not high, making it difficult to fully exert the interface toughening effect of the whiskers. Summary of the invention
[0004] Based on this, it is necessary to provide a silicon carbide composition, which, when used to prepare silicon carbide ceramics, can significantly reduce the porosity of the silicon carbide ceramics and further improve the fracture toughness and tensile strength of the silicon carbide ceramics.
[0005] Furthermore, a method for preparing a silicon carbide composition, a silicon carbide ceramic and a method for preparing the same are provided.
[0006] The first aspect of the present application provides a silicon carbide composition, comprising the following components: modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder; the modified silicon carbide whiskers include silicon carbide whiskers and a silicon dioxide film layer coated on the outer surface of the silicon carbide whiskers.
[0007] The above-mentioned silicon carbide composition includes modified silicon carbide whiskers, silicon carbide particles, sintering aids and binders. Among them, the modified silicon carbide includes silicon carbide whiskers and a silicon dioxide film layer coated on the outer surface of the silicon carbide whiskers. Among them, the surface characteristics of the silicon dioxide film are close to those of silicon carbide powder particles, and it is easy to react with moisture in the air to introduce hydroxyl groups, and then it can have good compatibility with the binder, and can form a mixed powder extrusion printing feed, improve printing stability, and provide a basis for the quality uniformity of ceramic finished products. Furthermore, during the sintering process, the silicon dioxide film can form a mullite liquid phase with the sintering aid, improve the sintering activity of the whiskers in the silicon carbide matrix, promote the improvement of material density, and reduce porosity. In addition, the silicon dioxide film on the surface of the whisker forms an oxide ceramic layer between the silicon carbide matrix after sintering, which improves the interface bonding strength between the whisker and the silicon carbide matrix, thereby further exerting the strengthening effect of the silicon carbide whisker.
[0008] In some embodiments, the thickness of the silicon dioxide film layer is 10 nm to 50 nm.
[0009] In some embodiments, the silicon carbide composition satisfies at least one of the following conditions:
[0010] (1) The silicon carbide composition comprises the following components by weight: 5 to 15 parts of the modified silicon carbide whisker, 70 to 92 parts of the silicon carbide particles, 3 to 10 parts of the sintering aid, and 18 to 25 parts of the binder;
[0011] (2) The diameter of the modified silicon carbide whisker is 0.2 μm to 1.0 μm;
[0012] (3) The aspect ratio of the modified silicon carbide whisker is 20 to 50;
[0013] (4) The average particle size D50 of the silicon carbide particles is 0.5 μm to 5.0 μm;
[0014] (5) The sintering aid is in granular form, and the average particle size D50 of the sintering aid is 0.5 μm to 2.0 μm;
[0015] (6) The sintering aid is selected from at least one of boric acid, boron, boron carbide, yttrium oxide and aluminum oxide;
[0016] (7) The binder comprises the following components, measured by weight: 50 to 80 parts of a filler, 20 to 40 parts of a backbone binder, and 1 to 5 parts of a dispersant; the filler is selected from at least one of microcrystalline wax, carnauba wax, and paraffin wax; the backbone binder is selected from at least one of high-density polyethylene, polypropylene, polystyrene, polyoxymethylene, and ethylene-vinyl acetate; the dispersant is selected from at least one of stearic acid, fatty acid esters, and polyacrylic acid.
[0017] A second aspect of the present application provides a method for preparing a silicon carbide composition, comprising the following steps:
[0018] The silicon carbide whisker is subjected to a pre-oxidation treatment to obtain a modified silicon carbide whisker; the modified silicon carbide whisker comprises a silicon carbide whisker and a silicon dioxide film layer coated on the outer surface of the silicon carbide whisker;
[0019] The modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder are mixed.
[0020] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0021] (1) The active reaction gas for the pre-oxidation treatment is oxygen; preferably, the oxygen gas flow rate is 15 sccm to 40 sccm;
[0022] (2) The temperature of the pre-oxidation treatment is 600°C to 800°C;
[0023] (3) The pre-oxidation treatment time is 10 min to 30 min;
[0024] (4) The oxygen gas flow rate is 15 sccm to 40 sccm.
[0025] In some embodiments, the step of mixing the modified silicon carbide whiskers, silicon carbide particles, a sintering aid, and a binder comprises:
[0026] First, the modified silicon carbide whiskers, silicon carbide particles and sintering aids are ultrasonically blended to obtain a composite powder; then the composite powder is mixed with the binder; preferably, the resonance frequency of the ultrasonic blending is 60 Hz to 80 Hz, and the mixing time is 5 min to 30 min.
[0027] The third aspect of the present application provides a silicon carbide ceramic, the raw materials for its preparation include the silicon carbide composition described in the first aspect; or, the raw materials for its preparation include the silicon carbide composition prepared by the preparation method described in the second aspect.
[0028] In some embodiments, the silicon carbide ceramic satisfies at least one of the following conditions:
[0029] (1) The porosity of the silicon carbide ceramic is 1% to 5.2%;
[0030] (2) The tensile strength of the silicon carbide ceramic is 440MPa~650MPa;
[0031] (3) The fracture toughness of the silicon carbide ceramic is 5.0 MPa·m 0.5~6.5MPa·m 0.5 .
[0032] A fourth aspect of the present application provides a method for preparing a silicon carbide ceramic, comprising the following steps:
[0033] The silicon carbide composition described in the first aspect or the silicon carbide composition obtained by the preparation method described in the second aspect is subjected to molding treatment, degreasing treatment and sintering treatment in sequence.
[0034] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0035] (1) The molding process is performed by 3D printing;
[0036] (2) The degreasing treatment includes solvent degreasing treatment and thermal degreasing treatment performed in sequence;
[0037] (3) The sintering temperature is 1900°C to 2100°C, and the sintering time is 1 to 3 hours;
[0038] (4) The solvent used in the solvent degreasing treatment is selected from at least one of n-hexane and n-heptane;
[0039] (5) The temperature of the solvent degreasing treatment is 20°C to 50°C;
[0040] (6) The solvent degreasing treatment time is 24h~60h;
[0041] (7) The temperature of the thermal degreasing treatment is 450°C to 600°C;
[0042] (8) The thermal degreasing treatment time is 5h~20h. DETAILED DESCRIPTION
[0043] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are given. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. It should be understood that the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0046] In the traditional preparation method of silicon carbide whisker reinforced silicon carbide ceramics, the addition of silicon carbide whiskers increases the difficulty of sintering, and is prone to poor sintering performance of silicon carbide ceramic materials and residual pores at the whiskers. In addition, silicon carbide whiskers are highly crystalline, and their bonding strength with the silicon carbide ceramic matrix is not high, making it difficult to fully exert the interface toughening effect of the whiskers.
[0047] Powder extrusion printing is an emerging ceramic 3D printing method, which mainly disperses the ceramic raw material powder in the binder to obtain the ability of plastic flow, and then combines the material extrusion printing process to achieve layer-by-layer deposition by heating the nozzle to obtain the ceramic body; finally, the ceramic material is prepared through degreasing and sintering processes. Compared with other ceramic 3D printing processes, powder extrusion printing has the advantages of low equipment cost, low requirements on the morphology of the ceramic feed for printing (that is, irregular shapes are also acceptable), strong designability of the blank components, and the orientation of anisotropic reinforcement components. Powder extrusion printing is an effective method for preparing complex structure whisker-reinforced silicon carbide ceramics.
[0048] However, after research, it was found that 1) after the introduction of silicon carbide whiskers, the uneven dispersion of ceramic raw material powder in the binder will cause nozzle clogging and poor printing stability. 2) After the addition of silicon carbide whiskers, the sintering performance of silicon carbide ceramic materials is poor, and residual pores are likely to exist at the whiskers. 3) Silicon carbide whiskers are highly crystalline, and their bonding strength with the silicon carbide ceramic matrix is not high, making it difficult to exert the interface strengthening effect of the whiskers.
[0049] Based on this, this application provides the following technical solutions:
[0050] In one embodiment of the present application, a silicon carbide composition is provided, comprising the following components: modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder; the modified silicon carbide whiskers include silicon carbide whiskers and a silicon dioxide film layer coated on the outer surface of the silicon carbide whiskers.
[0051] The silicon carbide composition includes modified silicon carbide whiskers, silicon carbide particles, sintering aids and binders. Among them, the modified silicon carbide includes silicon carbide whiskers and a silicon dioxide film layer coated on the outer surface of the silicon carbide whiskers. On the one hand, the surface properties of the silicon dioxide film are close to those of silicon carbide powder particles; and it is easy to react with moisture in the air to introduce hydroxyl groups, and then it can have good compatibility with the binder, and can form a uniformly mixed powder extrusion printing feed, improve printing stability, and provide a basis for the quality uniformity of ceramic products. On the second hand, during the sintering process, the silicon dioxide film can form a mullite liquid phase with the sintering aid, enhance the sintering activity of the whiskers in the silicon carbide matrix, promote the increase of material density, and reduce porosity. On the third hand, the silicon dioxide film on the surface of the whisker forms an oxide ceramic layer between the silicon carbide matrix after sintering, which improves the interface bonding strength between the whisker and the silicon carbide matrix, thereby further exerting the strengthening effect of the silicon carbide whisker.
[0052] It can be understood that in the modified silicon carbide whisker, the silicon dioxide film layer can be coated on part of the outer surface of the silicon carbide whisker or on the entire outer surface of the silicon carbide whisker.
[0053] In some embodiments, the thickness of the silicon dioxide film layer is 10 nm to 50 nm.
[0054] In some embodiments, the silicon carbide composition includes the following components, measured by weight: 5 to 15 parts of modified silicon carbide whiskers, 70 to 92 parts of silicon carbide particles, 3 to 10 parts of sintering aids, and 18 to 25 parts of binders.
[0055] As an example, the mass fraction of the modified silicon carbide whiskers can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 parts, or a value within the range consisting of any two of the above point values as end values.
[0056] As an example, the mass fraction of silicon carbide particles can be 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 or 92 parts, or a value within the range consisting of any two of the above point values as end values.
[0057] As an example, the mass fraction of the sintering aid can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, or a value within a range consisting of any two of the above point values as end values.
[0058] As an example, the mass fraction of the binder can be 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts, or a value within a range consisting of any two of the above point values as end values.
[0059] In some embodiments, the diameter of the modified silicon carbide whisker is 0.2 μm to 1.0 μm. As an example, the diameter of the modified silicon carbide whisker can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1.0 μm. Furthermore, the diameter of the modified silicon carbide whisker can be a range value consisting of any two of the above point values as end values. If the diameter of the oxidized whisker is too thick, the strengthening effect of the whisker will be reduced, and the interface bonding strength will be reduced (the internal high crystalline elastic modulus of the too thick whisker is significantly higher than the interface; the large thickness means that the stress of the interface will increase); at the same time, if it is too thin, the oxide film of the whisker will easily reduce the strength of the whisker and it will be easy to break.
[0060] In some embodiments, the aspect ratio of the modified silicon carbide whisker is 20 to 50. The aspect ratio is the ratio of the length of the modified silicon carbide whisker to its diameter. As an example, the aspect ratio of the modified silicon carbide whisker can be 20, 25, 30, 35, 40, 45 or 50. Further, the aspect ratio of the modified silicon carbide whisker can be a range value consisting of any two of the above point values as end values.
[0061] In some embodiments, the average particle size D50 of the silicon carbide particles is 0.5 μm to 5.0 μm. As an example, the average particle size of the silicon carbide particles can be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm. Further, the average particle size D50 of the silicon carbide particles can be a range value consisting of any two of the above point values as end values.
[0062] In some embodiments, the sintering aid is in particulate form.
[0063] In some embodiments, the average particle size D50 of the sintering aid is 0.5 μm to 2.0 μm. As an example, the average particle size D50 of the sintering aid can be 0.5 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm or 2.0 μm. Further, the average particle size D50 of the sintering aid can be a range value consisting of any two of the above point values as end values.
[0064] In some embodiments, the sintering aid is selected from at least one of boric acid, boron, boron carbide, yttrium oxide, and aluminum oxide.
[0065] In some embodiments, the binder includes the following components, by weight: 50 to 80 parts of filler, 20 to 40 parts of backbone binder, and 1 to 5 parts of dispersant.
[0066] As an example, the filler can be 50 parts, 52 parts, 54 parts, 55 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 70 parts, 72 parts, 75 parts, 76 parts, 78 parts or 80 parts. Further, the filler can be a range value consisting of any two of the above point values as end values.
[0067] In some embodiments, the filler is selected from at least one of microcrystalline wax, carnauba wax, and paraffin wax.
[0068] As an example, the backbone binder may be 20 parts, 22 parts, 25 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 35 parts, 36 parts, 38 parts or 40 parts. Further, the backbone binder may be a range value consisting of any two of the above point values as end values.
[0069] In some embodiments, the backbone binder is selected from at least one of high-density polyethylene, polypropylene, polystyrene, polyoxymethylene and ethylene-vinyl acetate. Preferably, the backbone binder is selected from high-density polyethylene and polypropylene. More preferably, the backbone binder is composed of 25wt% to 30wt% high-density polyethylene and 5wt% to 10wt% polypropylene in terms of mass percentage.
[0070] As an example, the dispersant may be 1 part, 2 parts, 3 parts, 4 parts or 5 parts. Further, the dispersant may be a range value consisting of any two of the above point values as end values. Preferably, the dispersant is 3 parts to 5 parts.
[0071] In some embodiments, the dispersant is selected from at least one of stearic acid, fatty acid esters, and polyacrylic acid.
[0072] In some embodiments, the binder includes the following components, calculated by weight percentage: 50 wt % to 80 wt % of filler, 20 wt % to 40 wt % of backbone binder, and 1 wt % to 5 wt % of dispersant.
[0073] In some embodiments, the silicon carbide composition described above can be used as feedstock for powder extrusion printing.
[0074] In one embodiment of the present application, a method for preparing a silicon carbide composition is provided, comprising the following preparation steps S10 to S20.
[0075] S10, pre-oxidizing the silicon carbide whisker to obtain a modified silicon carbide whisker; the modified silicon carbide whisker comprises a silicon carbide whisker and a silicon dioxide film layer coated on the outer surface of the silicon carbide whisker.
[0076] S20, mixing the modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder.
[0077] In some embodiments, the active reaction gas of the pre-oxidation treatment is oxygen.
[0078] In some embodiments, the temperature of the pre-oxidation treatment is 600° C. to 800° C. As an example, the temperature of the pre-oxidation treatment may be 600° C., 650° C., 700° C., 750° C. or 800° C., or may be any value within a range consisting of any two of the above point values as end values.
[0079] In some embodiments, the pre-oxidation treatment time is 10 min to 30 min. As an example, the pre-oxidation treatment time can be 10 min, 12 min, 15 min, 16 min, 18 min, 20 min, 22 min, 24 min, 25 min, 26 min, 28 min or 30 min. Further, the pre-oxidation treatment time can be a range value consisting of any two of the above point values as end values.
[0080] In some embodiments, the oxygen flow rate is 15 sccm to 40 sccm. As an example, the oxygen flow rate can be 15 sccm, 16 sccm, 18 sccm, 20 sccm, 22 sccm, 24 sccm, 25 sccm, 26 sccm, 28 sccm, 30 sccm, 32 sccm, 34 sccm, 35 sccm, 36 sccm, 38 sccm or 40 sccm, or can be any value within the range formed by any two of the above point values as end values.
[0081] In some embodiments, the pre-oxidation treatment is performed under protective gas conditions.
[0082] In some embodiments, the protective gas is argon or helium. Preferably, the protective gas is argon.
[0083] In some embodiments, the inlet gas flow rate of argon gas and the inlet gas flow rate of oxygen are (2-10):1.
[0084] In some embodiments, the above step S20, mixing the modified silicon carbide whiskers, silicon carbide particles, sintering aid and binder, includes the following steps S21-S22:
[0085] S21. First, the modified silicon carbide whiskers, silicon carbide particles and sintering aids are mixed to obtain a composite powder.
[0086] S22, mixing the composite powder with the binder.
[0087] In some embodiments, modified silicon carbide whiskers, silicon carbide particles, and sintering aids are mixed by sonic blending. Mixing by sonic blending is conducive to the uniform dispersion of modified silicon carbide whiskers in the composite powder, effectively inhibiting the silicon carbide composition from clogging the nozzle of the printing equipment during the powder extrusion printing process, and improving the printing stability. Compared with mechanical damage blending methods such as ball milling blending, sonic blending can inhibit the destruction of silicon carbide whiskers and ensure that silicon carbide whiskers fully exert their reinforcing effect in silicon carbide ceramics.
[0088] In some embodiments, the resonant frequency of the acoustic vibration mixing is 60 Hz to 80 Hz. As an example, the resonant frequency of the acoustic vibration mixing can be 60 Hz, 62 Hz, 64 Hz, 65 Hz, 66 Hz, 68 Hz, 70 Hz, 72 Hz, 74 Hz, 75 Hz, 76 Hz, 78 Hz or 80 Hz. Further, the resonant frequency of the acoustic vibration mixing can be a range value consisting of any two of the above point values as end values.
[0089] In some embodiments, the mixing time of the sonic blending is 5 min to 30 min. As an example, the mixing time of the sonic blending can be 5 min, 10 min, 15 min, 20 min, 25 min or 30 min. Further, the mixing time of the sonic blending can be a range value consisting of any two of the above point values as end values. Controlling the mixing time of the sonic blending can further control the mixing uniformity of the above components.
[0090] In some embodiments, the acceleration of the acoustic-vibration mixing is 60 to 90 g.
[0091] In some embodiments, in step S22, a mixer may be used to mix the composite powder and the binder.
[0092] In some embodiments, the step of mixing the composite powder with the binder using a mixer comprises:
[0093] First, the composite powder is added to a preheated internal mixer for the first mixing; then the binder is added for the second mixing.
[0094] In some embodiments, the first mixing temperature is 150°C to 200°C.
[0095] In some embodiments, the first mixing time is 15 min to 60 min.
[0096] In some embodiments, the second mixing temperature is 130°C to 190°C.
[0097] In some embodiments, the second mixing time is 60 min to 100 min.
[0098] In one embodiment of the present application, a silicon carbide ceramic is provided, and the raw material for preparing the silicon carbide composition is as follows.
[0099] In some embodiments, the silicon carbide ceramic includes a silicon carbide matrix phase and a silicon carbide whisker phase and an interface reinforcement phase therebetween, wherein the interface reinforcement phase includes silicon dioxide.
[0100] In some embodiments, the porosity of the silicon carbide ceramic is 1% to 5.2%. As an example, the porosity of the silicon carbide ceramic can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or 5.2%. It can also be any value within the range formed by any two of the above point values as end values. Preferably, the porosity of the silicon carbide ceramic is 2% to 3%.
[0101] In some embodiments, the tensile strength of silicon carbide ceramics is 440 MPa to 650 MPa. Preferably, the tensile strength of silicon carbide ceramics is 550 MPa to 650 MPa.
[0102] In some embodiments, the fracture toughness of the silicon carbide ceramic is 5.0 MPa·m 0.5 ~6.5MPa·m 0.5 Preferably, the fracture toughness of silicon carbide ceramic is 5.5 MPa·m 0.5 ~6.0MPa·m 0.5 .
[0103] In one embodiment of the present application, a method for preparing silicon carbide ceramics is provided, comprising the following step S30.
[0104] S30, sequentially subjecting the silicon carbide composition to molding, degreasing and sintering.
[0105] In some embodiments, the molding process is performed by 3D printing.
[0106] In some embodiments, the degreasing process includes a solvent degreasing process and a thermal degreasing process performed sequentially.
[0107] In some embodiments, the solvent of the solvent degreasing treatment is selected from at least one of n-hexane and n-heptane.
[0108] In some embodiments, the temperature of the solvent degreasing treatment is 20°C to 50°C.
[0109] In some embodiments, the solvent degreasing treatment time is 24h~60h. It can be understood that the solvent degreasing treatment time depends on the thickness of the product to be degreased. The thicker the product thickness, the longer the solvent degreasing treatment time. The solvent degreasing treatment time in this embodiment can have a good degreasing effect on a ceramic blank with a thickness of 10mm~20mm.
[0110] In some embodiments, the temperature of the thermal debinding process is 450°C to 600°C.
[0111] In some embodiments, the thermal degreasing treatment time is 5h~20h.
[0112] In some embodiments, the sintering process is performed at a temperature of 1900°C to 2100°C.
[0113] In some embodiments, the sintering time is 1 h to 3 h.
[0114] In some embodiments, when sintering is performed, the temperature is first increased from the temperature of the thermal debinding to 1900° C. to 2100° C. at a heating rate of 3° C. / min to 5° C. / min, and then maintained at that temperature for 1 h to 3 h.
[0115] In some embodiments, the silicon carbide composition is further granulated before the molding process.
[0116] In some embodiments, the granulation is performed in a granulator.
[0117] In some embodiments, the nozzle temperature of the pelletizer is set at 130°C to 150°C.
[0118] In some embodiments, the screw temperature of the pelletizer is set at 140°C to 160°C.
[0119] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0120] In order to better illustrate the present invention, the present invention is further described below in conjunction with the embodiments. The following are specific embodiments.
[0121] Example 1
[0122] (1) Pre-oxidation of silicon carbide whiskers:
[0123] Silicon carbide whiskers with an average diameter of 0.5 μm and an aspect ratio of 30 were placed in a sintered dish and pre-oxidized at 600°C at a heating rate of 3°C / min. The temperature was kept at this temperature for 30 minutes to obtain modified silicon carbide whiskers. The pre-oxidation atmosphere was a mixed flowing gas of oxygen and argon, the gas flow ratio of oxygen to argon was 2:8, and the gas flow rate was 100 sccm.
[0124] (2) Preparation of wax-based adhesive:
[0125] The raw materials are weighed and mixed according to the mass ratio: 60wt% microcrystalline wax, 30wt% high-density polyethylene, 5wt% polypropylene and 5wt% stearic acid to obtain a wax-based adhesive.
[0126] (3) Preparation of whisker reinforced silicon carbide composite powder:
[0127] The raw materials were weighed according to the mass ratio: 8 parts of modified silicon carbide whiskers, 87 parts of silicon carbide powder, 2 parts of boric acid, 3 parts of aluminum oxide and 19 parts of wax-based binder.
[0128] The modified silicon carbide whiskers, silicon carbide powder, boric acid and alumina were placed in an acoustic resonance device for acoustic resonance mixing; the resonant frequency of the acoustic resonance mixing was 60 Hz, the time was 10 min, and the acceleration was 60 gravitational acceleration (g); the whisker-reinforced silicon carbide composite powder was obtained. The average particle size D50 of the boric acid and alumina sintering aid powders was 1.0 μm; the average particle size D50 of the silicon carbide powder was 1.0 μm.
[0129] (4) Preparation of particle feed for powder extrusion printing:
[0130] The whisker-reinforced silicon carbide composite powder and the wax-based binder were poured into a preheated internal mixer for mixing; wherein the mixing temperature was 150°C and the mixing time was 60 minutes. The mixed mixture was then placed in a granulator, the screw temperature was set to 140°C and the nozzle temperature of the granulator was set to 150°C, and granulation was performed to obtain whisker-reinforced silicon carbide granule feed.
[0131] (5) 3D printed ceramic blanks:
[0132] The whisker-reinforced silicon carbide particles were fed into the feeding device of the powder extrusion printing equipment to print the ceramic blanks, wherein the printing nozzle temperature was 160°C, the printing substrate temperature was 100°C, the extrusion nozzle diameter was 0.6 μm, the printing rate was 30 mm / s, and the interlayer height was 0.5 times the nozzle diameter.
[0133] (6) The whisker-reinforced silicon carbide ceramic blank obtained by printing was subjected to solvent degreasing at a degreasing temperature of 40°C for a degreasing time of 30 hours, wherein the solvent was n-heptane.
[0134] (7) The sample after solvent debinding is subjected to thermal debinding and sintering densification: The sample after solvent debinding is placed in a furnace and heated to 500°C at a heating rate of 0.5°C / min and kept at this temperature for 3 hours for thermal debinding. Subsequently, the temperature is raised to 2000°C at a rate of 3°C / min and kept at this temperature for 2 hours for sintering densification. The sintering atmosphere is argon. Subsequently, whisker-reinforced silicon carbide ceramics with excellent performance can be obtained.
[0135] The whisker-reinforced silicon carbide ceramic obtained in this embodiment has a porosity of 3%, a tensile strength of 580 MPa, and a fracture toughness of 5.5 MPa·m 0.5 .
[0136] Example 2
[0137] Silicon carbide whiskers with an average diameter of 0.8 μm and an aspect ratio of 20 were placed in a flask and pre-oxidized at 800°C at a heating rate of 5°C / min. The temperature was kept at this temperature for 10 minutes to obtain modified silicon carbide whiskers. The pre-oxidation atmosphere was a mixed flowing gas of oxygen and argon, the gas flow ratio of oxygen to argon was 3:7, and the gas flow rate was 50 sccm.
[0138] (2) Preparation of wax-based adhesive:
[0139] The raw materials are weighed and mixed according to the mass ratio: 70wt% microcrystalline wax, 20wt% high-density polyethylene, 8wt% polypropylene and 2wt% stearic acid to obtain a wax-based adhesive.
[0140] (3) Preparation of whisker reinforced silicon carbide composite powder:
[0141] The raw materials were weighed according to the mass ratio: 12 parts of modified silicon carbide whiskers, 84 parts of silicon carbide powder, 4 parts of aluminum oxide and 22 parts of wax-based binder.
[0142] The modified silicon carbide whiskers, silicon carbide powder and alumina were placed in an acoustic resonance device for acoustic resonance mixing; the resonant frequency of the acoustic resonance mixing was 80 Hz, the time was 15 min, and the acceleration was 80 gravitational acceleration (g); the whisker-reinforced silicon carbide composite powder was obtained. The average particle size D50 of the alumina sintering aid powder was 1.5 μm; the average particle size D50 of the silicon carbide powder was 2.0 μm.
[0143] (4) Preparation of particle feed for powder extrusion printing:
[0144] The whisker-reinforced silicon carbide composite powder and the wax-based binder were poured into a preheated internal mixer for mixing; wherein the mixing temperature was 160°C and the mixing time was 80 minutes. The mixed mixture was then placed in a granulator, the screw temperature was set to 150°C and the nozzle temperature of the granulator was set to 160°C, and granulation was performed to obtain whisker-reinforced silicon carbide granule feed.
[0145] (5) 3D printed ceramic blanks:
[0146] The whisker-reinforced silicon carbide ceramic particles are fed into the feeding device of the powder extrusion printing equipment to print the ceramic blanks, wherein the printing nozzle temperature is 160°C, the printing substrate temperature is 80°C, the extrusion nozzle diameter is 0.8μm, the printing rate is 40mm / s, and the interlayer height is 0.4 times the nozzle diameter.
[0147] (6) The whisker-reinforced silicon carbide ceramic blank obtained by printing was subjected to solvent degreasing at a degreasing temperature of 50°C and a degreasing time of 40 hours, wherein the solvent was n-heptane.
[0148] (7) The sample after solvent debinding is subjected to thermal debinding and sintering densification. The sample after solvent debinding is placed in a furnace and heated to 550°C at a heating rate of 1.0°C / min and kept at this temperature for 2 hours for thermal debinding. Subsequently, the temperature is increased to 2100°C at a rate of 3°C / min and kept at this temperature for 2 hours for sintering densification; the sintering atmosphere is argon. Subsequently, whisker-reinforced silicon carbide ceramics with excellent performance can be obtained.
[0149] The whisker-reinforced silicon carbide ceramic obtained in this embodiment has a porosity of 2.5%, a tensile strength of 630 MPa, and a fracture toughness of 5.8 MPa·m 0.5 .
[0150] Example 3
[0151] (1) Pre-oxidation of silicon carbide whiskers:
[0152] Silicon carbide whiskers with an average diameter of 1.0 μm and an aspect ratio of 20 were placed in a flask and pre-oxidized at 700°C at a heating rate of 3°C / min. The temperature was kept at this temperature for 20 minutes to obtain modified silicon carbide whiskers. The pre-oxidation atmosphere was a mixed flowing gas of oxygen and argon, the gas flow ratio of oxygen to argon was 2:8, and the gas flow rate was 150 sccm.
[0153] (2) Preparation of wax-based adhesive:
[0154] The raw materials are weighed and mixed according to the mass ratio: 60wt% microcrystalline wax, 20wt% high-density polyethylene, 15wt% polypropylene and 5wt% stearic acid to obtain a wax-based adhesive.
[0155] (3) Preparation of whisker reinforced silicon carbide composite powder:
[0156] The raw materials were weighed according to the mass ratio: 15 parts of modified silicon carbide whiskers, 77 parts of silicon carbide powder, 3 parts of yttrium oxide, 5 parts of boron carbide and 25 parts of wax-based binder.
[0157] The modified silicon carbide whiskers, silicon carbide powder, yttrium oxide and boron carbide were placed in an acoustic resonance device for acoustic resonance mixing; wherein the resonance frequency of the acoustic resonance mixing was 80 Hz, the time was 15 minutes, and the acceleration was 80 gravitational acceleration (g); and the whisker-reinforced silicon carbide composite powder was obtained. The average particle size D50 of the yttrium oxide and boron carbide sintering aid powders was 2.0 μm; and the average particle size D50 of the silicon carbide powder was 5.0 μm.
[0158] (4) Preparation of particle feed for powder extrusion printing:
[0159] The whisker-reinforced silicon carbide composite powder and the wax-based binder were poured into a preheated internal mixer for mixing; wherein the mixing temperature was 160°C and the mixing time was 80 minutes. The mixed mixture was then placed in a granulator, the screw temperature was set to 150°C and the nozzle temperature of the granulator was set to 160°C, and granulation was performed to obtain whisker-reinforced silicon carbide granule feed.
[0160] (5) 3D printed ceramic blanks:
[0161] The whisker-reinforced silicon carbide ceramic particles were fed into the feeding device of the powder extrusion printing equipment to print the ceramic blanks, wherein the printing nozzle temperature was 155°C, the printing substrate temperature was 90°C, the extrusion nozzle diameter was 0.8 μm, the printing rate was 40 mm / s, and the interlayer height was 0.4 times the nozzle diameter.
[0162] (6) The whisker-reinforced silicon carbide ceramic blank obtained by printing was subjected to solvent degreasing at a degreasing temperature of 50°C and a degreasing time of 40 hours, wherein the solvent was n-heptane.
[0163] (7) The sample after solvent debinding is subjected to thermal debinding and sintering densification: The sample after solvent debinding is placed in a furnace and heated to 550°C at a heating rate of 1.0°C / min and kept at this temperature for 3 hours for thermal debinding. Then the temperature is raised to 2050°C at a rate of 4°C / min and kept at this temperature for 3 hours for sintering densification; the sintering atmosphere is argon. Subsequently, whisker-reinforced silicon carbide ceramics with excellent performance can be obtained.
[0164] The whisker-reinforced silicon carbide ceramic obtained in this embodiment has a porosity of 2%, a tensile strength of 620 MPa, and a fracture toughness of 6.0 MPa·m 0.5 .
[0165] Example 4
[0166] The preparation method of this embodiment is basically the same as that of Example 1, except that in this embodiment, when preparing the whisker-reinforced silicon carbide composite powder in step (2), acoustic resonance mixing is not performed; instead, the mixing is performed directly by ball milling, wherein the ball-to-material ratio is 3:1 and the ball milling time is 2 hours. The other preparation steps and process conditions are the same as those of Example 1.
[0167] Example 5
[0168] The preparation method of this embodiment is basically the same as that of Example 2, except that the ratio of the wax-based binder prepared in step (3) of this embodiment is different; the mass ratio of the wax-based binder in step (3) of this embodiment is: 70wt% microcrystalline wax, 28wt% polypropylene and 2wt% stearic acid. The other preparation steps and process conditions are the same as those of Example 1.
[0169] Comparative Example 1
[0170] The preparation method of this comparative example is basically the same as that of Example 1, except that this comparative example does not include the step of pre-oxidizing the silicon carbide whiskers. Other preparation steps and process conditions are the same as those of Example 1.
[0171] Performance Testing
[0172] Testing method for porosity of ceramic products: Test the porosity of ceramic products by Archimedes drainage method.
[0173] Test method for tensile strength of ceramic products: Measure in accordance with GB / T 23805-2009 Test method for tensile strength of fine ceramics at room temperature.
[0174] Test method for fracture toughness of ceramic products: Measure in accordance with GB / T 23806-2009 Test method for fracture toughness of fine ceramics.
[0175] The performance test data of the ceramic products prepared in each embodiment and comparative example are shown in Table 1:
[0176] Table 1
[0177]
[0178] From Table 1, it can be seen that the tensile strength of the ceramic products prepared in Examples 1 to 5 reaches 440 MPa to 630 MPa, and the fracture toughness reaches 5.0 MPa·m 0.5 ~6.0MPa·m 0.5 , having high mechanical properties. The porosity of the ceramics prepared in Examples 1 to 5 is 2.0% to 5.2%; the porosity is relatively low.
[0179] Comparative Example 1 adopts a preparation method that is basically the same as that of Example 1, except that the silicon carbide whiskers are not pre-oxidized in Comparative Example 1. The tensile strength of the ceramic product prepared therefrom is 420 MPa and the fracture toughness is 4.8 MPa·m 0.5 , which is much lower than the mechanical properties of the ceramic product prepared in Example 1. Moreover, the porosity of the ceramic product prepared in Comparative Example 1 is as high as 6.0%, which is much higher than the porosity of the ceramic product prepared in Example 1. It can be seen that pre-oxidation treatment of silicon carbide whiskers can significantly improve the mechanical strength of silicon carbide ceramic products and reduce the porosity of silicon carbide ceramic products, thereby improving the quality of silicon carbide ceramic products.
[0180] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0181] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A silicon carbide composition, characterized in that: The invention comprises the following components: modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder; the modified silicon carbide whiskers comprise silicon carbide whiskers and a silicon dioxide film layer coated on the outer surface of the silicon carbide whiskers.
2. The silicon carbide composition according to claim 1, characterized in that The thickness of the silicon dioxide film layer is 10nm-50nm.
3. The silicon carbide composition according to claim 1, characterized in that The silicon carbide composition satisfies at least one of the following conditions: (1) The silicon carbide composition comprises the following components by weight: 5 to 15 parts of the modified silicon carbide whisker, 70 to 92 parts of the silicon carbide particles, 3 to 10 parts of the sintering aid, and 18 to 25 parts of the binder; (2) The diameter of the modified silicon carbide whisker is 0.2 μm to 1.0 μm; (3) The aspect ratio of the modified silicon carbide whisker is 20 to 50; (4) The average particle size D50 of the silicon carbide particles is 0.5 μm to 5.0 μm; (5) The sintering aid is in granular form, and the average particle size D50 of the sintering aid is 0.5 μm to 2.0 μm; (6) The sintering aid is selected from at least one of boric acid, boron, boron carbide, yttrium oxide and aluminum oxide; (7) The binder comprises the following components, measured by weight: 50 to 80 parts of a filler, 20 to 40 parts of a backbone binder, and 1 to 5 parts of a dispersant; the filler is selected from at least one of microcrystalline wax, carnauba wax, and paraffin wax; the backbone binder is selected from at least one of high-density polyethylene, polypropylene, polystyrene, polyoxymethylene, and ethylene-vinyl acetate; the dispersant is selected from at least one of stearic acid, fatty acid esters, and polyacrylic acid.
4. A method for preparing a silicon carbide composition, characterized in that: The steps include: Pre-oxidizing the silicon carbide whisker to obtain a modified silicon carbide whisker; the modified silicon carbide whisker comprises a silicon carbide whisker and a silicon dioxide film layer coated on the outer surface of the silicon carbide whisker; The modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder are mixed.
5. The preparation method according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The active reaction gas for the pre-oxidation treatment is oxygen; preferably, the oxygen gas flow rate is 15 sccm to 40 sccm; (2) The temperature of the pre-oxidation treatment is 600°C to 800°C; (3) The pre-oxidation treatment time is 10 min to 30 min.
6. The preparation method according to any one of claims 4 to 5, characterized in that The step of mixing the modified silicon carbide whiskers, silicon carbide particles, a sintering aid and a binder comprises: First, the modified silicon carbide whiskers, silicon carbide particles and sintering aids are ultrasonically blended to obtain a composite powder; then the composite powder is mixed with the binder; preferably, the resonance frequency of the ultrasonic blending is 60 Hz to 80 Hz, and the mixing time is 5 min to 30 min.
7. A silicon carbide ceramic, characterized in that: The raw materials for its preparation include the silicon carbide composition as described in any one of claims 1 to 3; or, the raw materials for its preparation include the silicon carbide composition prepared by the preparation method as described in any one of claims 4 to 6.
8. The silicon carbide ceramic according to claim 7, characterized in that Silicon carbide ceramics meet at least one of the following conditions: (1) The porosity of the silicon carbide ceramic is 1% to 5.2%; (2) The tensile strength of the silicon carbide ceramic is 440MPa~650MPa; (3) The fracture toughness of the silicon carbide ceramic is 5.0 MPa·m 0.5 ~6.5MPa·m 0.5 .
9. A method for preparing silicon carbide ceramics, characterized in that: The steps include: The silicon carbide composition according to any one of claims 1 to 3 or the silicon carbide composition obtained by the preparation method according to any one of claims 4 to 6 is subjected to molding treatment, degreasing treatment and sintering treatment in sequence.
10. The method for preparing silicon carbide ceramics according to claim 9, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The molding process is performed by 3D printing; (2) The degreasing treatment includes solvent degreasing treatment and thermal degreasing treatment performed in sequence; (3) The sintering temperature is 1900°C to 2100°C, and the sintering time is 1 to 3 hours; (4) The solvent used in the solvent degreasing treatment is selected from at least one of n-hexane and n-heptane; (5) The temperature of the solvent degreasing treatment is 20°C to 50°C; (6) The solvent degreasing treatment time is 24h~60h; (7) The temperature of the thermal degreasing treatment is 450°C to 600°C; (8) The thermal degreasing treatment time is 5h~20h.